Prevalence of OCD among Academics in a Public University: A Moderating Role of Power of Influence - Abdullah, Mohd Zulkifli; Othman, Abdul Kadir; Abdul Rashid, Mas Anom; Saidon, Janiffa; Aluwi, Aini Hairianie; Haidir, Nurnazihah; Suryanto, Tulus (Advances in Social Sciences Research Journal, 2023)
Obsessive compulsive disorder (OCD) is a serious problem among children and adolescents. It will affect the sufferers’ social, emotional and academic functioning. In the long term, the problem will affect the individual, the family, the mental health system, and the society as the sufferers cannot play a significant role to contribute to the society. The present study was undertaken to investigate the main predictors of OCD among academics as they are also prone to suffering from this problem. At the same time, the present study was looking into the moderating effect of power of influence on the relationship between the four predictors and OCD among academics. Using 463 responses from academics in a public university, the study discovered that insecure attachment, external environment and role of genetics significantly contribute to OCD. Furthermore, power of influence is found to moderate the relationship between insecure attachment and OCD and between external environment and OCD among academics. The management of the university should encourage academics to involve in social activities in order to reduce the prevalence of OCD among the staff. Other implications are discussed in the paper.